Juridical Analysis Of Diffabel Wives In Article 57 Letter (B) Compilation Of Islamic Law - Amir Fiqih Alqadafi (STAIFAS-Press, 2018)
One of the strongest reasons for proposing polygamy as contained in article 57 letter b is that teh wife have a body defect (imperfect body) so that the husban can file a divorce and disability claim which is called diffable. There are regulations that regulate the similarity of rights before the law such as human rights, law number 4 of 1997 concerning persons with disabilities, the constitution of the Republik of Indonesia years 1945, law number 19 years 2011 concerning the ratification of disability conventions and law number 18 years 2016 concerning disability. Formulation of the problem is 1) what is the jurdical analysis of legal protection for women with disabilities in article 57 letter b KHI. 2) what is the solution or form of legal protection for women with disabilities in article 57 letter b KHI. Methodes is qualitative descreibed by the statute approach and conceptual aprroach. Type of library research and data collection in documentation and data analysis using content analiysis. Validity of data in credibility and data triangulation. Conclusion, the provisions of article 57 letter b conflict with human rights and disability law there are law number 4 years 1997 concerning persons with disabilities, the Republik Of Indonesia years 1945 artcle 27, law number 19 years 2011 concerning convention on the right of persons with disabilities and law number 8 years 2016 concerning disability and the jugde must tigthen not to grant the husban who wants to be polygamy for the reason of the disability. Keyword : Wives, Diffable, Compilation Of Islamic Law